The complex evaluation of lipid metabolism and blood coagulation system indicators for prediction and early diagnosis of the preeclampsia - Аксьонова, Анастасія Валеріївна; Венцківська, Ірина Борисівна; Платонова, Тетяна Миколаївна; Колесникова, Ірина Миколаївна; Наложитова, Олена Олегівна (ScienceRise: Medical Science, 2016)
Aim. To study informative and prognostic significance of lipid metabolism markers and coagulation system condition for PE early diagnostics in pregnant women during the second gestational trimester with risk evaluation of cardiovascular and metabolic pathologies in the given women category. Materials and methods. The analysis of blood serum samples in 267 pregnant women in II gestational trimester was carried out. The total cholesterol was determined by colorimetric method, enzymatic with CHOD/PAP, TG – by enzymatic colorimetric method, HDL – by homogeneous method, LDL – by direct method. VLDL concentration was calculated according to Fridvald’s formula: VLDL = TG/2.2. AF was calculated according to the formula: AF = (TC-HDL-c)/HDL-c. Pregnant women in II and III gestational trimesters also were examined concerning the general assessment of coagulation system condition – the concentration in blood plasma of D-dimer, soluble fibrin (SFMC), fibrinogen, FIPF, protein C activity, AT III, blood plasma clotting time was determined by PT test. Results. Of the 267 pregnant women, in 43 (16.1 %) of them, which formed the main group for research, the development of PE was found. Those pregnant women, who had PE clinical picture of the different severity levels, from the second trimester had significantly elevated TG, VLDL, AF levels, and low level of HDL in blood serum with high concentration of D-dimer (from 80 to 713 ng/ml), as well as protein C low activity in 17.6 % of pregnant women. In the third trimester pregnant women, having PE, fibrinogen content was significantly higher (4.4±1.02); the accumulation of a significant amount of SF, accompanied by FIPF presence in 40 % of pregnant women, was found in 50 % of pregnant women; a significant reducing (˂70 %) of the protein C activity was found in 48 % of patients. Conclusion. Both significant increasing of the soluble fibrin in blood plasma, and reducing of the protein C activity below 70 % are thrombosis prognostic indexes. The control of lipid metabolism and coagulation system indexes is necessary during all stages of pregnancy for estimation of PE risk and cardiovascular,cerebral vascular and metabolic complications prevention